English teachers’ professional identity incorporated with perceived anxiety in the context of flipped teaching: Scale development and model extension - Luo, Shuqiong; Zou, Di (International journal of applied linguistics, 2024)
Research examining teachers’ professional identity in the online context has recently increased; however, there have been few attempts (if any) to design a scale to assess foreign language teachers’ professional identity integrated with technology use in the flipped context. There have also been no extensions to the professional teacher identity model for flipped language teaching incorporated with psycho‐emotional factors. The current study first developed and validated an instrument for English teachers’ professional identity of technology integration in the flipped context (ETITF) to fill in the research gap that the majority of existing instruments for teachers’ professional identity have not considered the characteristics of technology integration in the flipped teaching environment in the subject area of English. Additionally, this present research also attempted to extend the professional teacher identity model by investigating the influence of the psycho‐emotional factor, namely, perceived anxiety of flipped teaching on professional teacher identity coped with technology in the flipped context by English teachers. Grounded by the identity theory and technology acceptance model, 233 in‐service English teachers from mainland China served to explore the constructs of the ETITF and the model extension with perceived anxiety. Results of exploratory factor analysis, first‐order, and second‐order confirmatory factor analysis supported a three‐dimension scale with 15 items: task perception (TP), motivation (M), and teacher self‐efficacy (SE). The results of the study revealed that the ETITF is valid and reliable that could be used by researchers, educators, and education institutions to gain a greater understanding of English language teachers’ professional development and can serve as a tool to support the procedures of developing teacher identity integrated with technology in the flipped context with specific items related to English teaching. The results of structural equation modeling indicated that task perception significantly predict English teachers’ motivation, while motivation showed positive influence on in‐service teachers’ self‐efficacy. This developed tool of ETITF and the extended professional identity with technology incorporation model may contribute to the development of flipped language teaching, which may provide implications for English educators and researchers to facilitate teachers’ effective technology integration in flipped English teaching. 近年來, 研究線上教學背景下教師專業身份的文獻逐漸增多;然而, 鮮有研究設計量表評估外語教師在翻轉課堂背景下整合技術的專業身份認同。而且, 現有翻轉語言教學專業教師身份模型缺乏考慮心理情感因素。本研究首先在英語學科領域開發並驗證了翻轉課堂模式下英語教師整合技術的專業身份認同量表 (ETITF) 。同時, 我們通過研究心理情感因素, 即翻轉教學感知焦慮對教師在翻轉課堂中整合技術時的專業身份的影響, 擴展了專業教師身份認同模型。 本研究基於身份認同理論和技術接受模型, 運用了ETITF量表結構和擴展模型, 探討了233名中國大陸在職英語教師的感知焦慮。探索性因數分析 (EFA) 以及一階和二階驗證性因數分析 (CFA) 的結果支持了ETITF量表的三維結構:任務感知 (TP) 、動機 (M) 和教師自我效能感 (SE) 。研究結果表明, ETITF量表具有良好的信度和效度, 可幫助研究人員、教育工作者和教育機構更深入地瞭解英語教師的專業發展, 可用于評估教師身份認同在翻轉英語教學中整合技術的發展。 結構方程模型的結果表明, 任務感知顯著預測了英語教師的動機, 而動機對在職英語教師的自我效能感有積極影響。ETITF量表和擴展後的專業教師身份 (技術整合) 模型有助於翻轉語言教學的發展, 可為英語教育工作者和研究人員提供促進英語教師在翻轉教學中有效整合技術的啟示。